Potential elucidation of a novel CTL epitope in HIV-1 protease by the protease inhibitor resistance mutation L90M. - Werner Smidt (PLoS ONE, 2013)
The combination of host immune responses and use of antiretrovirals facilitate partial control of human immunodeficiency virus type 1 (HIV-1) infection and result in delayed progression to Acquired Immunodeficiency Syndrome (AIDS). Both treatment and host immunity impose selection pressures on the highly mutable HIV-1 genome resulting in antiretroviral resistance and immune escape. Researchers have shown that antiretroviral resistance mutations can shape cytotoxic T-lymphocyte immunity by altering the epitope repertoire of HIV infected cells. Here it was discovered that an important antiretroviral resistance mutation, L90M in HIV protease, occurs at lower frequencies in hosts that harbor the B*15, B*48 or A*32 human leukocyte antigen subtypes. A likely reason is the elucidation of novel epitopes by L90M. NetMHCPan predictions reveal increased affinity of the peptide spanning the HIV protease region, PR 89-97 and PR 90-99 to HLA-B*15/B*48 and HLA-A*32 respectively due to the L90M substitution. The higher affinity could increase the chance of the epitope being presented and recognized by Cytotoxic T-lymphocytes and perhaps provide additional immunological pressures in the presence of antiretroviral attenuating mutations. This evidence supports the notion that knowledge of HLA allotypes in HIV infected individuals could augment antiretroviral treatment by the elucidation of epitopes due to antiretroviral resistance mutations in HIV protease.